2022
DOI: 10.3390/antiox11122498
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Proteomic Approach to Analyze Potential Antioxidant Proteins in Plant against Irradiation

Abstract: Gamma-ray irradiation is an effective and clean method of sterilization by inactivating microorganisms. It can also be applied to induce anti-oxidants for future application. In this study, the mung bean (Vigna radiata) was exposed to gamma-ray irradiation under the dose of 0, 5 or 10 kGy. With increasing irradiation doses, the concentrations of malondiadehyde decreased while the levels of total flavonoids and DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity increased. It has been shown that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Mass spectrometry-based proteomics combined with advanced bioinformatics is a powerful platform not only to determine the seed proteome profile from many legumes but also to identify, quantify, and demonstrate the conformational changes of many allergenic proteins. Despite being a crop high in nutrients, research has shown that mung beans are also cross-reactive with IgE. ,, Previous findings verified both naso-bronchial sensitization and the allergic reaction to mung bean consumption in clinical samples. ,, To date, only a handful of research papers have been published on the mung bean proteome. , However, to the best of our knowledge, no comparative analysis of the mung bean cultivar-specific seed proteome has been performed. The protein composition of mung bean seeds and sprouts was revealed in a recent study, which has enhanced our knowledge of the nutritional state of these plant parts and provided an in-depth understanding of the mechanisms involved in germination.…”
Section: Discussionmentioning
confidence: 94%
“…Mass spectrometry-based proteomics combined with advanced bioinformatics is a powerful platform not only to determine the seed proteome profile from many legumes but also to identify, quantify, and demonstrate the conformational changes of many allergenic proteins. Despite being a crop high in nutrients, research has shown that mung beans are also cross-reactive with IgE. ,, Previous findings verified both naso-bronchial sensitization and the allergic reaction to mung bean consumption in clinical samples. ,, To date, only a handful of research papers have been published on the mung bean proteome. , However, to the best of our knowledge, no comparative analysis of the mung bean cultivar-specific seed proteome has been performed. The protein composition of mung bean seeds and sprouts was revealed in a recent study, which has enhanced our knowledge of the nutritional state of these plant parts and provided an in-depth understanding of the mechanisms involved in germination.…”
Section: Discussionmentioning
confidence: 94%